1996
DOI: 10.1016/s0009-9236(96)90179-4
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and dynamic study of oral alprazolam with and without erythromycin in humans: In vivo evidence for the involvement of CYP3A4 in alprazolam metabolism*

Abstract: This study suggests that erythromycin, an inhibitor of CYP3A4, inhibits the metabolism of alprazolam, providing an in vivo evidence for the involvement of CYP3A4 in its metabolism. However, the kinetic change of alprazolam by erythromycin does not result in the pharmacodynamic change of this triazolobenzodiazepine, at least after single dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 29 publications
4
45
2
Order By: Relevance
“…Therefore, the present study clearly indicates the involvement of CYP3A4 in the metabolism of alprazolam, supporting the results of previous in vitro (von Moltke et al 1994) and in vivo (Yasui et al 1996) studies. Backman et al (1996) have compared the single oral dose pharmacokinetics of midazolam, which is a probe drug for the CYP3A4 activity (Watkins 1994), between epileptic patients taking carbamazepine or phenytoin and healthy volunteers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the present study clearly indicates the involvement of CYP3A4 in the metabolism of alprazolam, supporting the results of previous in vitro (von Moltke et al 1994) and in vivo (Yasui et al 1996) studies. Backman et al (1996) have compared the single oral dose pharmacokinetics of midazolam, which is a probe drug for the CYP3A4 activity (Watkins 1994), between epileptic patients taking carbamazepine or phenytoin and healthy volunteers.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the in vitro study by von Moltke et al (1994) has shown that ketoconazole, an inhibitor of CYP3A4 (Olkkola et al 1994;Watkins 1994), inhibits the 4-and ␣ -hydroxylation of alprazolam, suggesting that alprazolam is metabolized by CYP3A4. Furthermore, Yasui et al (1996) have reported that erythromycin, an inhibitor of CYP3A4 (Olkkola et al 1993;Watkins 1994), inhibits the metabolism of al-prazolam in healthy volunteers, providing in vivo evidence for the involvement of CYP3A4.…”
mentioning
confidence: 99%
“…[17,[27][28][29][30][31][32][33][34][35] or 77.7 ml/min for a man of 70 kg body weight. The CL R was calculated as 16.6 ml/ min as the product of CL oral and f e (21.4%) [11].…”
Section: Calculation Of CL Int In Vivo In Humansmentioning
confidence: 99%
“…Since alprazolam is one of the most commonly prescribed agents in this class, it is important to characterize the magnitude of the in vivo e¤ect of sertindole on the metabolism of this compound, which is extensively metabolized by CYP3A4 (Greenblatt et al 1996;Yasui et al 1996). Accordingly, this study was designed to assess the potential e¤ects of sertindole on alprazolam pharmacokinetics, after 1.0 mg single doses of alprazolam administered alone and in the presence of sertindole.…”
Section: Introductionmentioning
confidence: 99%